Virtual brain simulations reveal network-specific parameters in neurodegenerative dementias - Monteverdi, Anita; Palesi, Fulvia; Schirner, Michael; Argentino, Francesca; Merante, Mariateresa; Redolfi, Alberto; Conca, Francesca; Mazzocchi, Laura; Cappa, Stefano F.; Cotta Ramusino, Matteo; Costa, Alfredo; Pichiecchio, Anna; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction Neural circuit alterations lay at the core of brain physiopathology, and yet are hard to unveil in living subjects. The Virtual Brain (TVB) modeling, by exploiting structural and functional magnetic resonance imaging (MRI), yields mesoscopic parameters of connectivity and synaptic transmission. Methods We used TVB to simulate brain networks, which are key for human brain function, in Alzheimer’s disease (AD) and frontotemporal dementia (FTD) patients, whose connectivity and synaptic parameters remain largely unknown; we then compared them to healthy controls, to reveal novel in vivo pathological hallmarks. Results The pattern of simulated parameter differed between AD and FTD, shedding light on disease-specific alterations in brain networks. Individual subjects displayed subtle differences in network parameter patterns that significantly correlated with their individual neuropsychological, clinical, and pharmacological profiles. Discussion These TVB simulations, by informing about a new personalized set of networks parameters, open new perspectives for understanding dementias mechanisms and design personalized therapeutic approaches.